849 REM Behavioral Disorder as a Predictor of Lewy body Dementia- A Case Report. (3rd May 2021) - Koothirezhi, Rupa; Anne, Pratibha; Ho, Minh Tam; Monceaux, Brittany; Liendo, Cesar; Chernyshev, Oleg; Kilaikode, Sasikumar; Okorie, Ugorji
Abstract: Introduction: Dementia with Lewy bodies (DLB) is one of the most common types of degenerative dementia after Alzheimer's dementia. The core clinical features for diagnosis includes cognitive fluctuations, visual hallucinations, rapid eye movement (REM) sleep behavior disorder (RBD), and parkinsonism. Other symptoms include daytime drowsiness, longer daytime naps, prolonged staring spells, and episodes of disorganized speech. REM behavioral disorder (RBD) is commonly associated with DLB, occurring in 85 percent of individuals, often early in the course of the disease. It can precede the clinical diagnosis of DLB by up to 20 years. Report of case(s): A seventy-six-year-old female with a history of well controlled obstructive sleep apnea was diagnosed with REM behavioral disorder in 2012. She had presented with episodes of screaming, attempt to ambulate during sleep, resulting in injury. Her polysomnogram revealed evidence of REM without atonia and a screaming episode during REM. Her RBD symptoms were controlled with clonazepam and melatonin with less frequency of the RBD episodes. The patient gradually started noticing memory issues and by January 2020 she was diagnosed with dementia and was initiated on Aricept. Within 7 months of diagnosis of dementia, she started reporting vivid hallucinations that were not threatening or violent compared to her violent content of RBD. Physical exam revealed impaired cognitive function and mild intermittent resting tremor of the right hand. The neurological exam was normal including normal tone, strength, and gait. She also reported repeated falls and fractures. The diagnosis of Lewy body dementia was made based on the presence of 2 core clinical features. Conclusion: The current management of these conditions is mainly symptomatic. In the evolution of neurodegenerative disorder, RBD precedes other conditions like LBD, parkinsonism, etc. Research suggests that alpha-synuclein neurodegeneration is the common pathology behind these conditions. The understanding that RBD presents at the beginning of the evolution, provides us with a unique opportunity for preemptive treatment to prevent further degeneration in turn preventing the debilitation consequence like dementia, parkinsonism, neuroleptic sensitivity, and dysautonomia. Further research is needed for developing these early interventional strategies. Support (if any): NOne